(untitled) (JED (Jurnal Etika Demokrasi), 2021)
Abstract. The research background describes the social changes that accur in the Indonesian nation-state so rapidly, this is one the reasons it is easy to obtain means of communication and transportation so that if adolescents do not have strong filters they can srore norms and behavior, especially teenagers are very vulnerable to changes that are leads to a form of mischief. The purpose of this study describes: 1) the factors that cause delinquency in children; 2) forms of child delinquency; 3) how to deal with children’s delinquency; 4) implementation of multicultural values-based counseling intervention services; and 5) barriers to service delivery. This type of research is quantitative with a descriptive approach. The research subjects were students of SMA in Semarang City, while the data collection tools were observation, documentation, interviews, and questionnaires, while the data analysis technique used is descriptive percentages. The results obtained the conclusion that the handling of delinquency in high school children by counseling counseling through the intervention of multicultural values-based counseling services still needs serious attention from various parties and there needs to be a sustainable program, because there are still some counseling teachers who experience obstacles in the implementation of counseling intervention. Then alleviation of children’s deviant behavior in the form of delinquency has not been optimal. Keywords: Counseling Intervention, Multicultural Values. Abstrak. Latar belakang penelitian mendeskripsikan perubahan sosial yang terjadi di negara-bangsa Indonesia begitu cepat, hal ini salah satu sebabnya adalah mudahnya diperoleh sarana komunikasi dan transportasi sehingga jika remaja tidak memiliki filter kuat dapat melakukan penyimpanan terhadap norma dan perilaku, apalagi remaja sangat rentan terhadap perubahan yang mengarah pada bentuk kenakalan. Tujuan kajian ini mendeskripsikan: 1) faktor penyebab kenakalan anak; 2) bentuk kenakalan anak; 3) cara mengatasi kenakalan anak; 4) pelaksanaan layanan intervensi konseling berbasis nilai-nilai multikultural; dan 5) hambatan dalam pelaksanaan layanan. Jenis penelitian digunakan kuantitatif dengan desain deskriptif. Subjek penelitian adalah peserta didik SMA di Kota Semarang dengan alat pengumpul data observasi, dokumentasi, wawancara, dan angket, sedangkan teknik analisis data digunakan deskriptif persentase. Hasil penelitian diperoleh simpulan bahwa penanganan anak oleh guru BK melalui intervensi layanan konseling berbasis nilai-nilai multikultural masih diperlukan perhatian secara serius dari berbagai pihak dan perlu ada program tindak lanjut, sebab masih ada sebagian guru BK yang mengalami hambatan dalam pelaksanaan intervensi konseling, maka pengentasan perilaku menyimpang anak berupa kenakalan hasilnya belum maksimal. Kata Kunci: intervensi konseling, nilaii-nilai multikultural.